A Semantic Analysis of Rhetorical Devices in Charles Dickens’s A Tale of Two Cities - Salah Jameel Jabrael; Abbas Fadhil Lutfi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The goal of this research is to discover how rhetorical devices could be analysed semantically in some selected texts of Dickens’s ‘A Tale of Two Cities’. The data were collected from the novel. The researcher utilized a descriptive qualitative method to describe and investigate the rhetorical devices in this literary genre. Rhetorical devices are defined as a means of increasing the language's richness, diversity, clarity, power, and impact (Chetia 2015). Several semantic concepts and theories have been used to analyze rhetorical devices. These semantic theories and concepts include Lakoff and Johnson’s (1980), Kovecses’ (2010) and Saeed’s (2015) metaphor and metonymy, Cruse’s (2000) semantic anomaly, lexical relations such as synonymy, antonymy, polysemy, homonymy, hyponymy; and reference, sense, denotation and connotation. It is hypothesized that the meaning in rhetorical devices can be better manifested semantically. Consequently, the research discovered several well-known types of rhetorical devices in the novel such as metaphor, metonymy, synecdoche, antithesis, personification, repetition, and pun that can be analysed in the following semantic theories. This is because, in metaphor, the target domain could be understood through the source domain, whereas in metonymy, the target could be comprehended via the vehicle. Also, synecdoche was analysed via lexical relations where the part was hyponymy and the whole was superordinate; however, repetition was linked to reference, referent, and sense. Nonetheless, repetition, personification, and antithesis were analysed in terms of contradiction and semantic anomaly, while pun could be analysed in terms of polysemy and homonymy within lexical relations.